Pengaruh Mata Pelajaran Pembuatan Busana Industri dan Kewirausahaan terhadap Minat Berwirausaha Siswa Kelas XI SMKS: The Influence of Industrial Clothing Making and Entrepreneurship Subjects on the Entrepreneurial Interest of Class XI SMKS Students - Khairani Siska Pratiwi; Tri Utari Ismayuni (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
The entrepreneurial interest of Fashion Design Vocational High School students remains relatively low, despite being equipped with technical skills and entrepreneurial theory. This study aims to analyse the influence of Industrial Fashion Making and Entrepreneurship subjects on the entrepreneurial interest of grade XI Fashion Design students at Pangeran Antasari Vocational High School. The study used a quantitative approach with a correlational survey design, involving all 35 grade XI Fashion Design students as the total sample. Data were collected through a Likert scale questionnaire and analysed using classical assumption tests, multiple linear regression, t-tests, and F-tests. The results showed that the Industrial Fashion Making subject had a significant effect on entrepreneurial interest (p = 0.034 < 0.05), as did the Entrepreneurship subject (p = 0.000 < 0.05). Simultaneously, both variables had a positive and significant effect on students' entrepreneurial interest (F = 16.633, p < .05). The combination of technical sewing skills and entrepreneurial knowledge has been shown to increase students' self-confidence, creativity, and readiness to start independent businesses in the fashion industry. Research confirms that integrating productive learning and entrepreneurship effectively fosters an entrepreneurial mindset. Therefore, vocational curricula are recommended to incorporate project-based learning, product exhibitions, and business simulations to strengthen the entrepreneurial spirit and reduce the unemployment rate among vocational school graduates.